Phage therapy as a modern alternative to antibiotics - Hwang, Jiwon; Kim, Joohee (Edelweiss Applied Science and Technology, 2025)
The global rise of multidrug-resistant (MDR) bacterial infections has accelerated the pursuit of novel antimicrobial strategies. Bacteriophage therapy, which employs viruses that selectively infect and kill bacteria, has re-emerged as a promising alternative due to its host specificity and minimal disruption to commensal flora. Recent innovations in genetic engineering have enabled the creation of recombinant phages and lytic enzymes, enhancing their clinical efficacy. In particular, phage-derived lysins have demonstrated potent bactericidal effects against MDR pathogens, including MRSA and Acinetobacter baumannii, in both in vitro and in vivo models. Furthermore, engineered phages using CRISPR/Cas and synthetic biology are opening new frontiers, allowing for targeted eradication of resistance genes and improved biofilm disruption. These therapies are being explored not only for human infections but also for applications in food safety, veterinary medicine, and medical device sanitation. While host immune interactions and pharmacokinetics remain under investigation, current clinical data support the safety and therapeutic promise of phage-based approaches. This review highlights the biological principles, technological advancements, and practical implications of phage therapy as a modern solution to antibiotic resistance.